Influence of 2-naphthoic acid anchoring groups to the photovoltaic performance of zinc phthalocyanine-based photosensitizers in dye-sensitized solar cell - KOCA, ATIF (My University, 2023)
Two different zinc phthalocyanines bearing different numbers of 2-naphthoic acid anchoring groups at the peripheral positions were synthesized and characterized with UV–Vis, proton nuclear magnetic resonance (1H NMR), fouirer transform infrared (FT-IR), and matrix-assisted laser desorption/ionization mass (MALDI-TOF MS) spectroscopy. Then their electrochemical, and spectroelectrochemical performances were investigated to predict their suitability of them as photosensitizers in dye-sensitized solar cells (DSSC). In the voltammetric analysis results, [2,9,16-Tri-(4-carboxyethylphenoxy)-23-(4-[6-carboxy-2-naphtoxy]) substituted zinc(II) phthalocyanine (ZnPc(3)) and [2,9,16,23-tetra-(4-(6-carboxy-2-naphthoxy) substituted zinc(II) phthalocyanine (ZnPc(4)) illustrate similar electron transfer processes. The substituent environments of the complexes slightly influenced the position and reversibility of the redox couples. Redox processes of ZnPc(3) bearing unsymmetrical carboxyethylphenoxy and 2-naphthoic acid anchoring groups slightly shift towards the positive potentials concerning ZnPc(4) bearing symmetrical 2-naphthoic acid substituents. Peak positions of both complexes reflecting the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) positions indicate the suitability of the complexes for the efficient charge carrier transferring from these photosensitizers to the semiconductor and redox mediator in the DSSC. Pc-based spectroelectrochemical responses of the complexes supported the HOMO and LUMO positions for both neutral and electrogenerated ZnPc species. DSSC responses indicated that ZnPc(3), which has the asymmetric carboxyethylphenoxy and 2-naphthoic acid substituents, gave higher DSSC efficiency with short-circuit photocurrent density (JSC) (9.54 mA cm−2), open circuit potential (VOC) (697 mV), fill factor (FF) (51%), incident monochromatic photon-to-current conversion efficiency (IPCE) (51%), and power conversion efficiency (ƞ) (3.4%) parameters concerning ZnPc(4) bearing symmetric 2-naphthoic acid anchoring groups.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Analitik Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Analytical Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; MÜHENDİSLİK, KİMYASAL; KİMYA, ANALİTİK; ELEKTROKİMYA; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; CHEMISTRY; ENGINEERING, CHEMICAL; CHEMISTRY, ANALYTICAL; ELECTROCHEMISTRY; Fizik Bilimleri; Genel Kimya Mühendisliği; Physical Sciences; General Chemical Engineering; Anchoring group; Asymmetric phthalocyanine; Dye-sensitized solar cell; Spectroelectrochemistry; Synthesis; Asymmetric phthalocyanine; Anchoring group; Dye-sensitized solar cell; Electrochemistry; Spectroelectrochemistry